STRATEGIC COMPREHENSHIVE PENDIDIKAN DAN KETERAMPILAN KEPEMUDAAN DALAM MENGATASI MASALAH PENGANGGURAN - Basrowi Basrowi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2014)
The goals of this research are: (1) identify the productive and innovative program of youth policy, (2) finding the productive and innovative models of youth policy, and (3) finding the pursue factor and the support factor of youth program. The time of research spent five months, since July to November 2005. The steps of research are fourteen steps. Research located at  Bengkulu Province. Sample is taken by purposive for KUPP Program. Respondent composition are: young 40 respondent, bureaucrats 4 respondents, village head 4 respondents, partnership 3 respondents, student 4 respondents. The total sum of all respondents in every province are 55 respondents. The methods of data analysis uses qualitative and quantitative descriptive. Based on the result of research it concluded that government models of youth policy applied are: (1) able to absorb the employment and able to progress community prosperity, (2) able to build frame work of self government, capability, skill, motivation and work ethos.